NOX as a Therapeutic Target in Liver Disease - Deyamira Matuz-Mares; Héctor Vázquez-Meza; María Magdalena Vilchis-Landeros (MDPI AG, 2022)
The nicotinamide adenine dinucleotide phosphate hydrogen oxidase (NADPH oxidase or NOX) plays a critical role in the inflammatory response and fibrosis in several organs such as the lungs, pancreas, kidney, liver, and heart. In the liver, NOXs contribute, through the generation of reactive oxygen species (ROS), to hepatic fibrosis by acting through multiple pathways, including hepatic stellate cell activation, proliferation, survival, and migration of hepatic stellate cells; hepatocyte apoptosis, enhancement of fibrogenic mediators, and mediation of an inflammatory cascade in both Kupffer cells and hepatic stellate cells. ROS are overwhelmingly produced during malignant transformation and hepatic carcinogenesis (HCC), creating an oxidative microenvironment that can cause different and various types of cellular stress, including DNA damage, ER stress, cell death of damaged hepatocytes, and oxidative stress. NOX1, NOX2, and NOX4, members of the NADPH oxidase family, have been linked to the production of ROS in the liver. This review will analyze some diseases related to an increase in oxidative stress and its relationship with the NOX family, as well as discuss some therapies proposed to slow down or control the disease's progression.